Establishment of drivers' comfort through automotive ergonomics - Ahmad Rasdan, Ismail (Universiti Malaysia Pahang, 2014)

(untitled)
One of the most important contributions of ergonomics knowledge to the automobile design process is the characterization of physical size of driver and his/her preferred postures [9]. An experiment conducted by Costanzo et. al (1999) detected the different levels of muscular fatigue between correct and incorrect postures [2]. Awkward postures and high vibration exposure while in driving position might result in high risk condition for musculoskeletal disorders [4]. There have been many past research and experiments conducted in driver's car posture [1,3,4,5,6,7,8,10,11]